(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Dental implants must be positioned in areas with a high rate of success. The current retrospective study's objective was to identify risk variables that might have an impact on dental implant success rates as well as the prevalence of dental implant failure among patients who had their implants placed more than 10 years ago.Materials & Methods: The current retrospective analysis involved 1230 dental implants placed in 728 patients of both sexes. The implant's length, diameter, placement, and bone quality were all noted. Risk factors were noted, including smoking behaviour, diabetes history, hypertension, etc.Results: Dental implants were inserted in 415 male patients (764, or 62%) and 313 female patients (466, or 38%). Dental implants failed in 81 (10.6%) male patients and 34 (7.3%) female patients. Statistically, it was significant. Greatest failure of dental implant was observed with lengths of 10 mm in 42 cases (17%), 10–11.5 mm in 30 cases (9%), and >11.5 mm in 54 cases (8.2%). The variation was substantial.Greatest failure of dental implant was observed with diameters of 3.75 mm or below (12.4%), 3.75 mm to 4.5 mm (8.1%), and > 4.5 mm (7.5%). It was determined that the difference was significant (P 0.05). Type IV bone had the highest rate of dental implant failure (16.8%), subsequently type three (9.4%), type two (8.2%), and type one bone (6.4%). The variation was determined to be important (P 0.05). Smoking (41%) and CVDs (35.7%), diabetes (30.8%), and hypertension (18.8%) were the two factors that caused the most dental implant failures, while healthy individuals had the lowest failure rate (2.9%). ANOVA analysis revealed a variation among implant failure depending on risk factors that was significantly different (P 0.05).Conclusion: Researchers discovered that dental implants have a high rate of success. Dental implants with a length of less than 10.0 mm, a diameter of less than 3.75 mm, and patients with diabetes and type four bone had the highest failure rates.